Temperature-dependent f-electron evolution in CeCoIn5 via a comparative infrared study with LaCoIn5 - Myounghoon Lee; Yu-Seong Seo; Seulki Roh; Seokbae Lee; Jihyun Kim; Junwon Kim; Tuson Park; Ji Hoon Shim; Jungseek Hwang (Results in Physics, 2023)
We investigated CeCoIn5 and LaCoIn5 single crystals, which have the same HoCoGa5-type tetragonal crystal structure, using infrared spectroscopy. However, while CeCoIn5 has 4f electrons, LaCoIn5 does not. By comparing these two material systems, we extracted the temperature-dependent electronic evolution of the f electrons of CeCoIn5. We observed that the differences caused by the f electrons are more obvious in low-energy optical spectra at low temperatures. We introduced a complex optical resistivity and obtained a magnetic optical resistivity from the difference in the optical resistivity spectra of the two material systems. From the temperature-dependent average magnetic resistivity, we found that the onset temperature of the Kondo effect is much higher than the known onset temperature of Kondo scattering (≃200 K) of CeCoIn5. Based on momentum-dependent hybridization, the periodic Anderson model, and a maximum entropy approach, we obtained the hybridization gap distribution function of CeCoIn5 and found that the resulting gap distribution function of CeCoIn5 was mainly composed of two (small and large) components (or gaps). We assigned the small and large gaps to the in-plane and out-of-plane hybridization gaps, respectively. We expect that our results will provide useful information for understanding the temperature-dependent electronic evolution of f-electron systems near Fermi level.